A new method for improving the dynamics of superconducting magnetic bearings. - Komori, M. (IEEE Transactions on applied superconductivity)
This paper describes a new method for improving the dynamics of passive type superconducting magnetic bearings (SMBs). The SMBs are composed of two kinds of superconductors and a permanent magnet. The superconductors of the SMBs were field-cooled in the experiments. After the field-cooling, impulse responses were performed for various horizontal displacements. Then, changes in stiffness and damping coefficient of the SMBs were investigated. From the experimental results, it is found that the stiffness and the damping coefficient are affected by the maximum displacements and by use of sintered superconductors, respectively. The stiffness and the damping coefficient are also evaluated by using frequency responses. Then, the results by frequency responses are compared with those by impulse responses. As a result, it is found that we can control bearing stiffness by changing horizontal displacements and damping coefficient by using sintered superconductors.